Morphological Diversity and Virulence of Colletotrichum spp. Causing Anthracnose in Chilli Pepper in Coastal Purworejo, Indonesia - Nur Kholida Wulansari; Nur Prihatiningsih; Heru Adi Djatmiko; Endang Mugiastuti (Universitas Panji Sakti, 2026)
Anthracnose, caused by Colletotrichum spp., is one of the most destructive diseases affecting chilli peppers and can result in significant yield losses, particularly in coastal agroecosystems where climatic factors favor the development and spread of this pathogen. This study examined the diversity and virulence of Colletotrichum populations in the coastal region of Purworejo Regency, Central Java, by investigating the severity of anthracnose as well as the morphological diversity and virulence of Colletotrichum spp. in the coastal region of Purworejo Regency, Central Java, Indonesia. Disease surveys were conducted in chilli-producing areas located in three subdistricts along the coast, followed by the isolation and morphological characterization of the pathogen, as well as an evaluation of its pathogenicity against healthy chilli fruits under laboratory conditions, using a purposive sampling design and a completely randomized design for laboratory testing. The results showed that anthracnose was widespread across all locations, with disease severity ranging from low (1%) in Grabag and Purwodadi subdistricts at Location 1 to very high (75%) in Purwodadi subdistrict at Location 2. Nineteen Colletotrichum isolates were isolated from fruit exhibiting symptoms. They showed significant variation in colony morphology—white, black, gray, and orange on the reverse side of Petri dishes—with textures ranging from cottony to sparse; conidia were oval, fusiform, and crescent-shaped; and conidiomata production was observed in some isolates. Pathogenicity tests showed that all isolates except two exhibited varying levels of virulence, ranging from moderate to high, with the highest virulence of 73.09% observed in the isolate from Purwodadi Subdistrict.